Role of NK cells in cord blood transplantation and their enhancement by the missing ligand effect of the killer-immunoglobulin like receptor - Yokoyama, Hisayuki (Frontiers in Genetics, 2022)
Natural killer (NK) cells are the first lymphocytes reconstituted after allogenic hematopoietic stem cell transplantation (HSCT). Especially, in cord blood transplantation (CBT), the increase in the number of NK cells is sustained for a long period. Although there are conflicting results, many studies show that early reconstitution of NK cells is associated with favorable CBT outcomes, suggesting that maximizing NK cell functions could improve the CBT outcome. Killer immunoglobulin-like receptors (KIRs) include inhibitory and stimulatory receptors, which can regulate NK-cell activity. Because some of the KIRs have HLA class I as their ligand, the KIR–ligand interaction on NK cells can be lost in some cases of CBT, which results in the activation of NK cells and alters HSCT outcome. Thus, effects of KIR–ligand mismatch under various conditions have been widely examined; however, the results have been controversial. Among such studies, those using the largest number of CBTs showed that HLA–C2 (KIR2DL1–ligand) mismatches have a favorable effect on the relapse rate and overall survival only when the CBT used methotrexate for graft-versus-host disease prophylaxis. Another study suggested that KIR–ligand mismatch is involved in reducing the relapse of acute myeloid leukemia, mediated by reactivation of cytomegalovirus. These results indicate that activation of NK cells by KIR–ligand mismatch may have favorable effects on CBT outcomes and could help enhance the NK-cell function.